PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Call Center PT. Swakarya Insan Mandiri Semarang) - Sri Utorowati, 13.05.51.0140; Waruwu, Penunjang (Students' Journal of Economic and Management, 2018)
This study analyzes the influence of motivation, work environment and job satisfaction on employee performance. The object of this research is PT. Swarangya Insan Mandiri Semarang. Technique the sample of the research is using “accidental sampling” were 100 respondents as samples with the collecting data which use a questionnaire (survey) by means of spreading questionnaire to respondents in order to obtain information. The purpose of this research to know the influence of motivation, work environment and job satisfaction for employee performance. Data collected analysis using a correlation coefficient for testing validity, the formula cronbach alpha to test reabilitas instrument, regression analysis to test how major for a partial for free variable tested with regression analysis. The results showed that motivation influential positive and significantly to the employee performance, work environment influential positive and significantly to the employee performance, job satisfaction influential positive and significantly to the employee performance Keywords: Motivation, work environment, job satisfaction and the employee performance